Antimicrobial and anti-biofilm properties of polypropylene meshes coated with metal-containing DLC thin films - Cazalini, Elisa M.; Miyakawa, Walter; Teodoro, Guilherme R. [UNESP]; Sobrinho, Argemiro S. S.; Matieli, José E.; Massi, Marcos; Koga-Ito, Cristiane Y. [UNESP] (Springer Nature, 2017)
Abstract: A promising strategy to reduce nosocomial infections related to prosthetic meshes is the prevention of microbial colonization. To this aim, prosthetic meshes coated with antimicrobial thin films are proposed. Commercial polypropylene meshes were coated with metal-containing diamond-like carbon (Me-DLC) thin films by the magnetron sputtering technique. Several dissimilar metals (silver, cobalt, indium, tungsten, tin, aluminum, chromium, zinc, manganese, tantalum, and titanium) were tested and compositional analyses of each Me-DLC were performed by Rutherford backscattering spectrometry. Antimicrobial activities of the films against five microbial species (Candida albicans, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis) were also investigated by a modified Kirby-Bauer test. Results showed that films containing silver and cobalt have inhibited the growth of all microbial species. Tungsten-DLC, tin-DLC, aluminum-DLC, zinc-DLC, manganese-DLC, and tantalum-DLC inhibited the growth of some strains, while chromium- and titanium-DLC weakly inhibited the growth of only one tested strain. In-DLC film showed no antimicrobial activity. The effects of tungsten-DLC and cobalt-DLC on Pseudomonas aeruginosa biofilm formation were also assessed. Tungsten-DLC was able to significantly reduce biofilm formation. Overall, the experimental results in the present study have shown new approaches to coating polymeric biomaterials aiming antimicrobial effect. Graphical Abstract: [InlineMediaObject not available: see fulltext.].